2018
DOI: 10.3390/met8121078
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Scrap in Hot Metal under Linz–Donawitz (LD) Steelmaking Conditions

Abstract: One of the main charging materials of the Linz–Donawitz oxygen steelmaking process (LD) is scrap. Scrap acts as a coolant for the exothermic reactions inside the LD vessel and as an iron source in addition to hot metal. The optimization of the LD process is focused, amongst other factors, on thermodynamic and kinetic modelling. The results of simulations have to be validated in close to reality laboratory-scale experiments. A study was made on the dissolution behavior of common steel scrap in carbon-saturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 10 publications
(11 reference statements)
0
26
0
Order By: Relevance
“…They based their assumption concerning turbulent conditions on geometric and physical parameters of the experiment using the theory of Taylor‐Couette flows. Based on the published system, a turbulent mixing regime was established . The mass transfer coefficients are listed in Table and are comparable in the range of previous investigations using a similar experimental setup …”
Section: Mass Transfermentioning
confidence: 53%
See 4 more Smart Citations
“…They based their assumption concerning turbulent conditions on geometric and physical parameters of the experiment using the theory of Taylor‐Couette flows. Based on the published system, a turbulent mixing regime was established . The mass transfer coefficients are listed in Table and are comparable in the range of previous investigations using a similar experimental setup …”
Section: Mass Transfermentioning
confidence: 53%
“…Penz et al carried out dissolution tests using S235JR construction steel samples in hot metal in ref. They reported that after 20 s of immersion time, the core of the specimen has the same temperature as the liquid hot metal; thus, only mass transfer is in action. Similar results were also reported by Penz et al .…”
Section: Mass Transfermentioning
confidence: 99%
See 3 more Smart Citations